“Do Not Use in Case of Emergency”: Five Underlying Pathologies in the Peruvian Emergency Arbitrator Proceeding - Collantes Rojas, Christian M. (2020)
The emergency arbitrator proceeding has managed to enhance and provide efficiency and celerity to the system of precautionary measures, for the benefit of effective jurisdictional protection prior to the constitution of the arbitral tribunal. However, such proceeding could be undermined, and the interim relief granted be frustrated, due to bad practices.In this paper, the author analyses the existence of pathological scenarios in the Peruvian emergency arbitration proceeding, which may undermine its purpose. Some of these pathological scenarios refer to guerrilla tactics used by the party affected with the precautionary measure, others are covered by regulatory gaps and some of them are based on the procedure’s own regulations, by defrauding it through the irregular exercise of a right.